The Development and Validation of the Spiritual Values Scale for Primary School Children in the Turkish Context - Zengin, Erdal (Springer, 2025)
The present study was conducted with the objective of developing and validating the Spiritual Values Scale for Primary School Children (SVS-PSC) as a reliable and culturally sensitive instrument to assess spiritual values among Turkish primary school students. The scale development process followed a multi-phase psychometric framework, including the generation of an item pool, expert review, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and criterion-related validation. A study was conducted with 400 children aged 9-11 in order to ascertain the structure of the EFA. The results of the study revealed a unidimensional structure which explained 47.716% of the total variance, with item loadings ranging from .512 to .690. The KMO value (.806) and Bartlett's test (chi 2 = 613.902, p < .001) indicated the suitability of the data for factor analysis. The CFA, based on a sample of 260 children, supported the one-factor model with acceptable fit indices (chi 2/df = 2.231; RMSEA = .080; CFI = .914; GFI = .930). The criterion validity of the scale was examined through administration of the Spiritual Robustness Scale to a sample of 39 children. A significant positive correlation (r = .371, p < .001) was identified, suggesting that the scale effectively captures aspects of spiritual resilience and internal strength. The SVS-PSC demonstrated high reliability (Cronbach's alpha = .831), and item-total correlations ranged from .396 to .588. The findings of this study indicate that the SVS-PSC is a psychometrically robust tool for evaluating core spiritual values such as honesty, gratitude, empathy, and responsibility in children. The scale provides researchers and educators with a valid instrument with which to understand spiritual development and foster character education in primary school settings.
Keywords: Spiritual values; Primary school children; Scale validation; Turkey; Spiritual resilience; Child development